Linha, choque e mônada: tempo e espaço na obra tardia de Walter Benjamin - Georg Otte (1994)
A comparative analysis of Walter Benjamin's later texts, trying to show that the Benjaminian criticism of the concept of linear time may be applied also to the concept of linear text and that the author aims at substituting temporal linearity by spatial complexity.